A clinical analysis of three methods for repairing deciduous molars - TAO Nannan, LI Wenlei, CHEN Xing, SONG Weijian, ZHOU Hongyan (Kouqiang yixue)
Objective To discuss the efficacy of direct resin filling restoration, improved atraumatic restorative treatment (ART), and Hall technique in treating deciduous molars in children. Methods A total of 120 children with 180 deciduous molars who came to the Department of Oral Surgery of our hospital from January 2023 to August 2023 were selected and randomly divided into three groups: direct resin filling restoration group(40 people, 60 teeth), improved ataumatic restorative treatment group(40 people, 62 teeth), and Hall technique group(40 people, 58 teeth). The behavioral performance classification and degree of anxiety of the children during the treatment process and the treatment time were compared among the three groups. The clinical efficacy after 3 months, 6 months, and 12 months of treatment was compared and the reasons for failure were analyzed. Results The treatment time of the Hall technique group was significantly shorter than that of the improved ART group and direct filling group, and the differences in treatment time of the three groups had statistical significance(P<0.05). The Hall technique and improved ART technique were more easily accepted by the children, and the degree of anxiety and behavioral performance classification of the three groups had statistically significant differences(P<0.05). At the 12-month follow-up, the success rate of the direct filling restoration group was significantly different from that of the improved ART technique group and the Hall technique group, and the difference was statistically significant(P<0.05). However, the success rate of the improved ART technique group was not significantly different from that of the Hall technique group(P>0.05). Conclusion The success rate of the improved ART technique group and the Hall technique group is higher than that of the direct filling restoration group, and is more easily accepted by children. The pain level and degree of anxiety are lighter, and the treatment time of the Hall technique is shorter, which is more conducive to the repair of tooth decay.